MODEL PEMBELAJARAN PENDIDIKAN JASMANI UNTUK MENINGKATKAN FLEKSIBILITAS SENAM LANTAI SISWA DI INDONESIA: PHYSICAL EDUCATION LEARNING MODEL TO IMPROVE FLEXIBILITY OF STUDENTS IN FLOOR GYMNASTICS IN INDONESIA - Nur Aina; Mashud (UNIB Press, 2025)
This study aims to conduct a Systematic Literature Review (SLR) in order to synthesize the literature and formulate a physical education learning model to improve junior high school students’ flexibility in floor exercises. The method used is a systematic literature review based on the analysis of six selected relevant journal articles. The process involved extracting key findings related to the importance of flexibility, learning challenges faced by junior high school students, the effectiveness of teaching methods and styles, as well as the influence of motivation. The synthesis results confirm that flexibility is crucial for floor exercise movements (such as backbends and forward rolls), and that junior high school students face both physical and psychological challenges. The literature highlights the effectiveness of various approaches, such as the use of media, practice style, and peer tutoring, along with the importance of motivation. These findings provide the conceptual foundation for designing the model. The conclusion of this study is that the synthesis of SLR findings offers a solid basis for formulating an adaptive and effective learning model to improve junior high school students’ flexibility in floor exercises through a comprehensive approach that considers both physical and psychological aspects.